2015
DOI: 10.1002/bab.1437
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a horseradish peroxidase resistant toward hydrogen peroxide by saturation mutagenesis

Abstract: Horseradish peroxidase (HRP) with a variety of potential biotechnological applications is still isolated from the horseradish root as a mixture of different isoenzymes with different biochemical properties. There is an increasing demand for preparations of high amounts of pure enzyme but its recombinant production is limited because of the lack of glycosylation in Escherichia coli and different glycosylation patterns in yeasts which affects its stability parameters. The goal of this study was to increase the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…For N255D on the other hand, Capone et al [19] observed almost the same catalytic activity compared to the benchmark enzyme (1.1-fold increase). N268D had a 2-fold increased turnover number (k cat ) when compared to the non-mutated rHRP and the same trend was shown by Asad et al [20], where a 2.6-fold enhanced k cat with phenol/4-aminoantipyrine was reported. The slightly enhanced catalytic efficiency of N57S, when compared to the benchmark rHRP (1.2-fold), is in accordance with Capone et al [19] (1.4-fold).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…For N255D on the other hand, Capone et al [19] observed almost the same catalytic activity compared to the benchmark enzyme (1.1-fold increase). N268D had a 2-fold increased turnover number (k cat ) when compared to the non-mutated rHRP and the same trend was shown by Asad et al [20], where a 2.6-fold enhanced k cat with phenol/4-aminoantipyrine was reported. The slightly enhanced catalytic efficiency of N57S, when compared to the benchmark rHRP (1.2-fold), is in accordance with Capone et al [19] (1.4-fold).…”
Section: Resultssupporting
confidence: 78%
“…They described variants N13D and N268D, which showed increased catalytic efficiency with phenol/4-aminoantipyrine and were both more stable in terms of hydrogen peroxide and heat tolerance. A follow-up study identified N268G, which showed 18-fold higher resistance towards hydrogen peroxide and 2.5-fold higher thermal stability [20]. Capone et al [19] performed a profound investigation of N -glycosylation mutants in P. pastoris , where asparagines at eight sites were replaced by aspartic acid, serine or glutamine.…”
Section: Introductionmentioning
confidence: 99%
“…Saturation mutagenesis techniques provide full access to all amino acids by using degenerate codons covering a comprehensive collection of amino acids (15)(16)(17). Such approaches frequently identify multiple nucleotide replacements (MNRs) within a codon to be superior to SNRs in a variety of contexts (16,(18)(19)(20)(21)(22)(23)(24)(25)(26). Recent technological advances in DNA synthesis and sequencing have enabled more detailed surveys of a complete systematic saturation mutagenesis of a gene, permitting the interrogation of the full mutational landscape at single amino acid resolution (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of activity upon glycosylation has been observed for various enzymes 5,52 but little is known how glycan addition at sites remote from the active site are influencing enzyme activity. Indeed, it has been observed previously for HRP when plant produced enzyme is compared to the recombinant form 16,21,28,57 but with little attention paid and no rationale provided for such an observation. Thus, the main cause of this activity enhancement is largely unknown.…”
Section: Discussionmentioning
confidence: 99%